Terapia ocupacional para reducir el estrés en los adultos mayores que asisten al Centro Municipal de atención al adulto mayor número 1 período, marzo- julio 2015 - Ojeda Jaramillo, Christian David (2016)
The thesis of name: OCCUPATIONAL THERAPY TO DECREASE THE STRESS IN OLDER ADULTS THAT ARE GOING TO THE MUNICIPAL CENTER OF ATTENTION OF OLDER ADULT NUMBER 1 PERIOD, MARCH - JULY 2015. It was applied in this population, because some people was nervous, irritable, pessimistic, exhausted, this symptoms characteristic of stress, for that is more difficult your quality of life. This thesis was made in the mix investigation; it was used the type of study descriptive and explanatory; the methods that it was used there are in three areas: theoretical diagnosis, design-planning proposal and evaluation-assessing of itself, for that it was used scientific methods, also was used theoretical methods as the synthetic, inductive, logical, analytic descriptive, hermeneutical, dialectical, phenomenological; empiric methods as: observation, the scale of stress perceived more knew like PSS-14, which it provided the measurement of the phenomenon to categorize and a daily record of making staff to evaluation the activities in the proposal. The sample it was selection using a reagent, for which was not used a probabilistic statistics, coinciding the sample number and population 23 people. The description statistic lets organized the result get it. It was could conclude that the most of the users the center decrease levels of stress after to application the therapy workshop, for this is really important that continue using to improve the life of this person.